Pattern Of Religious Character Development at The Aisyiyah Orphanage In Banua Anyar Village Banjarmasin City - Jumriani Jumriani; Ersis Warmansyah Abbas; Uswatun Isnaini; Mutiani Mutiani; Bambang Subiyakto (STAI Hubbulwathan Duri, 2022)
The problem of neglected children is still a crucial problem seen from the complexity of the problem and the increasing quantity of neglected children. The social problems of neglected children are because they cannot meet the needs of children socially and economically due to internal and external factors of the family. Children's basic needs include survival, growth and development, protection, and participation. The existence of orphanages managed by individuals, groups, and organizations can provide educational space for neglected children. One of the main things is the development of religious character. Religion is the central aspect children must have as a filter to distinguish between good and bad things to live during the times. This article aims to identify the pattern carried out at the Putri Aisyiyah Orphanage, Banua Anyar Village, to instill a religious character. The approach used in this study is qualitative by describing the study's results to describe the cultivation of character education in children at the Aisyiah Orphanage in Banua Anyar Village. Data collection techniques through observation of activities in the orphanage, interviews with administrators, caretakers of the orphanage, and documentation in recordings and pictures. Data analysis uses data reduction based on research objectives, data presentation in words equipped with tables and figures, and data verification by concluding. Finally, test the validity of the data using triangulation, the extension of observation. The study results ensure that the coaching pattern is carried out through three methods, namely habituation, example, and giving advice. In this case, the role of the caregiver affects the growth and development of the religious character of the foster child. Therefore, the Aisyiyah orphanage in Banua Anyar Village has an essential role for foster children to develop religious characters valid for the present and the future.